2021
DOI: 10.1155/2021/7832672
|View full text |Cite
|
Sign up to set email alerts
|

Infection Risk Prediction Model for COVID-19 Based on an Analysis of the Settlement of Particles Generated during Dental Procedures in Dental Clinics

Abstract: Background. The health emergency declaration owing to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has drawn attention toward nosocomial transmission. The transmission of the disease varies depending on the environmental conditions. Saliva is a recognized SARS-CoV-2 reservoir in infected individuals. Therefore, exposure to fluids during dental procedures leads to a high risk of contagion. Objective. This study aimed to develop an infection risk prediction model for COVID-19 based on an analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…However, the literature is unclear regarding how far aerosols can spread. 24 25 26 27 The SARS-CoV-2 virus has been isolated from the saliva of infected patients, 28 including asymptomatic individuals, 29 but the potential viral load in the aerosols produced by dental procedures is unknown. Initial studies have also indicated that the virus could remain viable for hours in the aerosols and for days on surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature is unclear regarding how far aerosols can spread. 24 25 26 27 The SARS-CoV-2 virus has been isolated from the saliva of infected patients, 28 including asymptomatic individuals, 29 but the potential viral load in the aerosols produced by dental procedures is unknown. Initial studies have also indicated that the virus could remain viable for hours in the aerosols and for days on surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the limited supply of antigen test kits during the fourth wave of the COVID-19 pandemic in Thailand led our team to take an efficacious strategy and practical approach to using such limited kits in this study. Those patients who are set up to receive aerosol-generating dental treatment have a higher chance of spreading viral particles in the dental treatment environment ( 21 , 22 ). Thus, the screening for SARS-CoV-2 infection was focused on these groups, despite the fact that all patients possess the risk of infection.…”
Section: Discussionmentioning
confidence: 99%